2- Between Ethnic Essentialism and Environmental Racism: Oil and the ‘Glocalisation’ of Environmental Justice Discourse in Nigeria - Akpan, Wilson (African Sociological Review, 2006)
This paper examines the ‘state’ of environmental justice discourse in Nigeria, focussing on the ways in which the concept of environmental racism has been deployed to explain corporate and state conduct in the upstream petroleum sector. The paper shows how, in trying to make environmental racism relevant to the debates on socio-ecological abuses, and attendant grassroots resistance in Nigeria, some analysts have inserted it into ethnic discourse. Thus, what might have been a problematic concept in the Nigerian context now sits within a ‘familiar’, albeit not wholly appropriate framework – an ethnic model, which typically portrays grassroots struggles in sub-Saharan Africa as driven by invidious primordial concerns. Based on a recent ethnographic study conducted in some of Nigeria’s better known oil-producing communities, and on relevant secondary data, the paper shows how the application of environmental racism at once illuminates and distorts the social character of petroleum-related grassroots struggles in Nigeria. Importantly, it shows how decades of naked greed, failed ‘background institutions’ and disastrous political governance in Nigeria have, paradoxically, not sufficiently instigated in the scholarly community a fundamental rethink of the sociology of dispossession in Nigeria.